Fabrication and optimization of 3D printed gelatin methacryloyl microneedle arrays based on vat photopolymerization - Dilruba Baykara; Dilruba Baykara; Tuba Bedir; Tuba Bedir; Elif Ilhan; Elif Ilhan; Mehmet Eren Mutlu; Mehmet Eren Mutlu; Oguzhan Gunduz; Oguzhan Gunduz; Oguzhan Gunduz; Roger Narayan; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Microneedles (MNs) are micrometer-sized arrays that can penetrate the skin in a minimally invasive manner; these devices offer tremendous potential for the transdermal delivery of therapeutic molecules. Although there are many conventional techniques for manufacturing MNs, most of them are complicated and can only fabricate MNs with specific geometries, which restricts the ability to adjust the performance of the MNs. Herein, we present the fabrication of gelatin methacryloyl (GelMA) MN arrays using the vat photopolymerization 3D printing technique. This technique allows for the fabrication of high-resolution and smooth surface MNs with desired geometries. The existence of methacryloyl groups bonded to the GelMA was verified by 1H NMR and FTIR analysis. To examine the effects of varying needle heights (1000, 750, and 500 µm) and exposure times (30, 50, and 70 s) on GelMA MNs, the height, tip radius, and angle of the needles were measured; their morphological and mechanical properties were also characterized. It was observed that as the exposure time increased, the height of the MNs increased; moreover, sharper tips were obtained and tip angles decreased. In addition, GelMA MNs exhibited good mechanical performance with no breakage up to 0.3 mm displacement. These results indicate that 3D printed GelMA MNs have great potential for transdermal delivery of various therapeutics.